CLINICAL CHARACTERISTICS OF PATIENTS WITH AMYOTROPHIC LATERAL SCLEROSIS IN THE REPUBLIC OF SRPSKA - Lepir, Igor; Malešević, Milica; Dominović Kovačević, Aleksandra (Medicinski podmladak, 2019)
Introduction: Amyotrophic lateral sclerosis (ALS) is a rare, fatal and progressive neurodege-nerative disease which begins due to selective damage to motor neurons. The disease beginsas spinal (spinal cervical, spinal lumbosacral and spinal thoracic form) and bulbar form. Thediagnosis is set by using revised El Escorial criteria.Aim: Aims of the paper were determining demographic characteristics of ALS patients, ca-tegory of the disease and functional disability of patients using Revised Amyotrophic LateralSclerosis Functional Rating Scale (ALSFRS-R).Material and methods: In this cross-sectional study, medical histories of ALS patients,which were diagnosed at the Clinic of Neurology of the University Clinical Center of theRepublic of Srpska, were examined. Demographic characteristics, initial form of thedisease, category of disease (using revised El Escorial criteria), functional disability (usingALSFRS-R) and dia-gnostic delay were analyzed.Results: This study included 30 patients, 20 (67%) were male, 10 (33%) were female. TheALS began at 57 ± 12 years, and average diagnostic delay was 10 months. The diseasestarted as a spinal form in 26 (87%) patients, out of which 13 (43%) had spinal cervical, 12(40%) spinal lumbosacral and 1 (3%) spinal thoracic form of disease. The initial bulbarform was reported in 4 (13%) patients. The average ALSFRS-R score was 33,5. Patients witha spinal lumbosacral form of the disease had statistically significant lower score ofALSFRS-R (p = 0.048) which indicates bigger functional motoric disablement, comparedto other forms of disease. Low values of ALSFRS-R are correlated with more accuratediagnosis, according to the revised El Escorial criteria.Conclusion: Results of this study showed that ALS is more frequent and occurs earlierin men. The disease most commonly started as spinal cervical form. Patients with spinallumbo-sacral form of the disease had significantly lower values of ALSFRS-R whichindicates a faster progression of the disease. As patients acquire lower ALSFRS-R scores andgreater disability, they progress to the definite ALS category.